THE EFFECT OF DISTRICT OWN-SOURCE REVENUE AND BALANCE FUNDS ON PUBLIC WELFARE BY CAPITAL EXPENDITURE AND ECONOMIC GROWTH AS AN INTERVENING VARIABLE IN SPECIAL DISTRICT OF YOGYAKARTA - Badrudin, Rudy; Kuncorojati, Irawan (Jurnal Manajemen dan Kewirausahaan, 2017)
The transfer funds from the central government which is not followed by own source revenues, causes the autonomous district too dependent on the central government funds. This study aims to determine the effect of own-source revenue and balance funds on public welfare by capital expenditure and economic growth as an intervening variable in Special District of Yogyakarta. The source of data is secondary data during 2006 to 2013 and using Partial Least Square to test hypotheses. The result showed that own-source revenue has not significant effect on capital expenditure but has significant effect on economic growth and public welfare; balance funds has significant effect on capital expenditure but has not significant effect on economic growth and public welfare; capital expenditure has significant effect on economic growth but has not significant effect on public welfare; and economic growth has not significant effect on public welfare.